2020
DOI: 10.1021/acs.langmuir.0c01767
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-Free Transparent Superhydrophobic Nanocomposite Coatings from Mesoporous Silica

Abstract: In recent decades, there has been a growing interest in the development of functional, fluorine-free superhydrophobic surfaces with improved adhesion for better applicability into real-world problems. Here we compare two different methods, spin coating and aerosol assisted chemical vapor deposition (AACVD), for the synthesis of transparent fluorine-free superhydrophobic coatings. The material was made from a nanocomposite of (3-aminopropyl)triethoxysilane (APTES) functional mesoporous silica nanoparticles and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 82 publications
(189 reference statements)
0
20
0
Order By: Relevance
“… 36 The technique has been widely used to study superhydrophobic surfaces. 27 , 37 39 The aerosolized precursor is delivered and deposited to a substrate in the AACVD chamber during the process. 36 Depending on the type of precursor, single or multiple deposition processes have been used to produce superhydrophobic surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 36 The technique has been widely used to study superhydrophobic surfaces. 27 , 37 39 The aerosolized precursor is delivered and deposited to a substrate in the AACVD chamber during the process. 36 Depending on the type of precursor, single or multiple deposition processes have been used to produce superhydrophobic surfaces.…”
Section: Introductionmentioning
confidence: 99%
“… 36 Depending on the type of precursor, single or multiple deposition processes have been used to produce superhydrophobic surfaces. 27 , 37 39 For example, Tombesi et al . introduced a layer-by-layer deposition using 3-methacryloxypropyltrimethoxysilane and tetraethyl orthosilicate (TEOS) while Zhuang et al described a single-step deposition using PDMS and TEOS.…”
Section: Introductionmentioning
confidence: 99%
“…22−25 Stable fluorinated groups decrease the van der Waals potential with the result that electrostatic interactions limit contact between the solid and liquid phases, resulting in wider contact angles. 26 However, several recent reports have shown that the risk of the use of fluorine-based compounds involves risks of environmental contamination and human health issues such as incurable diseases (e.g., thyroid disease, cancer, and Alzheimer's syndrome), immune disorders, and hormonal disorders. 27−32 In addition, a rough-textured surface and low surface energy are required to form a hydrophobic surface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The hydrophobic surface modification method that has been widely used so far is the use of fluorine compounds such as poly­(tetrafluoroethylene) (PTFE, Teflon) and perfluoroalkyl groups. Because fluorine has a small atomic diameter (42 pm) and a large electronegativity (3.98), it is advantageous for lowering the surface free energy. Stable fluorinated groups decrease the van der Waals potential with the result that electrostatic interactions limit contact between the solid and liquid phases, resulting in wider contact angles . However, several recent reports have shown that the risk of the use of fluorine-based compounds involves risks of environmental contamination and human health issues such as incurable diseases (e.g., thyroid disease, cancer, and Alzheimer’s syndrome), immune disorders, and hormonal disorders. In addition, a rough-textured surface and low surface energy are required to form a hydrophobic surface.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, recent research efforts have begun to emphasize superhydrophobic materials fabricated from non-fluorinated components. Alternatives to perfluorinated materials include hydrophobic alkyl chains, poly­(dimethyl siloxane), and even inherently hydrophilic materials such as silicon when incorporated into doubly re-entrant surface structures . Despite the contributions from those reported works, it remains a major challenge to simultaneously achieve superhydrophobicity and high inherent mechanical durability, especially using non-fluorinated materials.…”
Section: Introductionmentioning
confidence: 99%